Penyulingan Dan Karakterisasi Minyak Atsiri Dari Kulit Jeruk Peras (Citrus x microcarpa Bunge) Dengan Metode Distilasi Uap Air - Mahfuzah, Rauzatul Laziah; Elwina, Elwina; Dewi, Ratni (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
In this study, squeezed orange peel was distilled by water vapor distillation method to extract its essential oil, which can be used as an antioxidant. The fixed variable is the weight of 3 kg of squeezed orange peel with a size of ±1 cm-2 cm and a temperature of 125 ℃ and a pressure of 1.2 bar. Independent variables are the ratio of squeezed orange peel:water 1:2, 1:3, 1:4, 1:5, sampling time, 3 hours 4 hours 5 hours and 6 hours. The dependent variables are essential oil yield analysis, essential oil density analysis, essential oil refractive index analysis, essential oil component analysis by GC-MS and essential oil antioxidant analysis by DPPH method. The most yield and volume of squeezed orange peel oil was obtained at a ratio of 1: 2 with a sampling time of 6 hours, namely as much as 1.2289% and 43 mL. From the density obtained, all samples of squeezed orange peel essential oil meet SNI 06-0009-1987 while the closest to ISO 3140, 2019 is the 1:2 ratio of squeezed orange peel essential oil. From the refractive index obtained, the closest to SNI 06-0009-1987 and ISO 3140, 2019 is the 1:2 ratio of squeezed orange peel essential oil. From the component test and antioxidant test, the highest dl-Limonene composition was obtained at a ratio of 1:5 with a sampling time of 6 hours, namely 54.94% and very strong antioxidant strength of 49.07 µg/mL.